Dokumen dalam Perspektif Ilmu Komunikasi - Yudhawasthi, Ciwuk Musiana (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACT The definition of a document has changed quite significantly over time. The meaning of document has become increasingly widespread, not only for inanimate two- and three-dimensional objects but also includes living three-dimensional objects. In 1992 Blasius Sudarsono formulated an axiom which initially aimed to explain the library phenomenon from the perspective of Communication Science. This axiom is now used by Sudarsono as the axiom of "Document Theory and Documentation Activities" (Documentation). This research uses a qualitative approach and aims to explore document phenomena in the realm of Communication Science based on Sudarsono's axioms. Data collection was carried out through an in-depth interview with a key informant named Blasius Sudarsono. To enrich the data, literature studies, observations, and documentation were also carried out. Interviews and observations were carried out during the process of making the book as well as socializing Blasius Sudarsono's thoughts in the ‘Bincang Senang Kepustakawanan ‘forum to various stakeholders in the 2015-2016 period. The research results show that there is an intersection between the concepts of Documents, New Documentation Science, and Communication Science. From the perspective of communication science, the meaning of objects in the world is influenced by the knowledge and experience of each human being. Any object is considered a document as long as humans interpret it as a document, especially if the object fulfills the aspects of a document, namely: indexicality, plurality, fixity, documentality, and productivity. Humans often get caught up in differences in communication symbols, however, the most important thing is the substance, the meaning.   ABSTRAK Definisi dokumen mengalami perubahan yang cukup signifikan. Saat ini pengertian dokumen pun menjadi semakin meluas, tidak hanya pada objek mati dua dan tiga dimensi, namun mencakup juga objek hidup tiga dimensi. Pada tahun 1992 Blasius Sudarsono merumuskan sebuah aksioma yang awalnya bertujuan menjelaskan fenomena perpustakaan dalam sudut ilmu komunikasi. Aksioma tersebut kini digunakan Sudarsono sebagai aksioma “Teori Dokumen dan Kegiatan Dokumentasi” (Kedokumentasian). Penelitian ini menggunakan pendekatan kualitatif dan bertujuan mengeksplorasi fenomena dokumen dalam ranah ilmu komunikasi berdasarkan aksioma Sudarsono. Pengumpulan data dilakukan melalui wawancara mendalam dengan informan kunci bernama Blasius Sudarsono. Untuk memperkaya data dilakukan pula studi literatur, observasi dan dokumentasi. Wawancara dan observasi dilakukan selama proses pembuatan buku serta sosialisasi pemikiran Blasius Sudarsono dalam forum Bincang Senang Kepustakawanan kepada beragam stakeholder pada kurun waktu 2015-2016. Hasil penelitian menunjukkan terdapat irisan antara konsep Dokumen, Ilmu Dokumentasi Baru dengan Ilmu Komunikasi. Dalam perspektif ilmu komunikasi, makna terhadap objek di dunia dipengaruhi oleh pengetahuan dan pengalaman setiap manusia. Objek apapun selama manusia memaknainya sebagai dokumen, dapat dikatakan sebagai dokumen, terutama apabila objek tersebut memenuhi aspek-aspek dokumen, yaitu indexicality, plurality, fixity, documentality, productivity. Manusia seringkali terjebak pada perbedaan simbol atau lambang komunikasinya, padahal yang terpenting adalah substansi, yaitu pemaknaan.